Magnetic bioactive glass nano-heterostructures: a deeper insight into magnetic hyperthermia properties in the scope of bone cancer treatment. (20th June 2022) - Vergnaud, Florestan; Kesse, Xavier; Jacobs, Aurélie; Perton, Francis; Begin-Colin, Sylvie; Mertz, Damien; Descamps, Stéphane; Vichery, Charlotte; Nedelec, Jean-Marie
Abstract : γ-Fe2 O3 @SiO2 –CaO NPs were designed. They show predicable and effective magnetic hyperthermia properties in clinically relevant conditions and promote hydroxyapatite growth in SBF. They could be used to heal bone defects due to tumor resection. Abstract : Primary bone cancers commonly involve surgery to remove the malignant tumor, complemented with a postoperative treatment to prevent cancer resurgence. Studies on magnetic hyperthermia, used as a single treatment or in synergy with chemo- or radiotherapy, have shown remarkable success in the past few decades. Multifunctional biomaterials with bone healing ability coupled with hyperthermia property could thus be of great interest to repair critical bone defects resulting from tumor resection. For this purpose, we designed superparamagnetic and bioactive nanoparticles (NPs) based on iron oxide cores (γ-Fe2 O3 ) encapsulated in a bioactive glass (SiO2 –CaO) shell. Nanometric heterostructures (122 ± 12 nm) were obtained through a two-step process: co-precipitation of 16 nm sized iron oxide NPs, followed by the growth of a bioactive glass shell via a modified Stöber method. Their bioactivity was confirmed by hydroxyapatite growth in simulated body fluid, and cytotoxicity assays showed they induced no significant death of human mesenchymal stem cells after 7 days. Calorimetric measurements were carried out under a wide range of alternating magnetic field amplitudes and frequencies, considering clinically relevant parameters, and some were made in viscous medium (agar) to mimic the implantation conditions. The experimental specific loss power was predictable with respect to the Linear Response Theory, and showed a maximal value of 767 ± 77 W gFe −1 (769 kHz, 23.9 kA m −1 in water). An interesting value of 166 ± 24 W gFe −1 was obtained under clinically relevant conditions (157 kHz, 23.9 kA m −1 ) for the heterostructures immobilized in agar. The good biocompatibility, bioactivity and heating ability suggest that these γ-Fe2 O3 @SiO2 –CaO NPs are a promising biomaterial to be used as it is or included in a scaffold to heal bone defects resulting from bone tumor resection.